Enhancing Disaster Preparedness using Murphys Law (Global Journal of Human-Social Science, 2014)
Murphy's Law is commonly expressed that 'if anything can go wrong it will' and is believed to have been founded between 1940 and 1950. This law has been associated with many problems and failures. Murphy's Law can at times be seen as a threat of impending dangers and disasters since disasters can strike anytime and anywhere. Disasters can include workplace violence, fires, arson, and flooding, drought, terrorist acts, hazardous material spills e.t.c. Murphy's Law can be a reminder for a holistic and integrated approach to disaster preparedness and mitigation so that communities participate in the process using local materials and being part of the process. This makes the communities resilient. At work place, implementing a continuous programme of testing and role-playing, safety and security professionals involved in contingency planning can dramatically improve their organizations chances of cutting loss when a disaster strikes. Strategic planning and contingency plans have come about so that Murphy's Law does not prevail. However, Murphy's Law can prevail if there is no disaster preparedness, mitigation and when contingency plans are filed away in cabinets and forgotten.
Keywords: murphy’s law; disasters; holistic; integrated approach; disaster preparedness; mitigation; conti-n gency plans; strategic planning